LATERAL MENISCUS TEARS IN ACL INJURED KNEE - Tapasvi, Sachin; Shekhar, Anshu; Pilar, Anoop (The Hip and Knee Journal, 2021)
Anterior cruciate ligament (ACL) tears can be associated with injuries to the lateral meniscus (LM) in about 20-30% cases. The lateral meniscus is more mobile than the medial and besides contributing to load transmission, it also stabilizes the knee in pivot-shift testing. The LM tears more often in the acute setting and its incidence does not rise in cases of chronic ACL instability. Lateral meniscus tears can be minor or major depending how severely the knee function gets impaired. Major tears are the complete radial tears, longitudinal bucket handle tears and posterior root tears. Male gender, high body mass index and contact injury mechanism are all risk factors for an LM tear. Anatomic factors which can contribute to LM tears include a high posterior tibial slope, varus malalignment and greater asymmetry between medial and lateral slopes. The lateral meniscus must be saved and repaired whenever possible to prevent residual knee instability and progressive lateral compartment arthritis, which can set in soon after a meniscectomy. The development of techniques and technology have rendered most tears amenable to repair. Longitudinal tears can be repaired by the all-inside or inside-out technique and the needles and devices must be inserted through a high anteromedial or transpatellar portal to prevent injury to the popliteal neurovascular structures. A lateral safety incision must always be used for inside-out repairs. Radial tears can be repaired by  two horizontal sutures, a cross stich, a cross-tag or a hash-tag suture configuration. Lateral meniscus posterior root repairs are repaired by transtibial technique, either by drilling an independent anatomic tunnel or the sutures pulled out via the ACL tibial tunnel. The lateral meniscus has high healing rates and repairs yield improvement in functional outcome, beside delaying radiographic arthritis.